Modelagem do Despacho Econômico de Energia Elétrica em Minirredes - Silva, Cristiane dos Santos (2018)
Over time the demand for electric energy has increased and new energy sources are being introduced into the Power System, which is increasingly interconnected and with a more diversified topology with the insertion of minigrids. In view of this scenario, one of the main objectives for operation in the electricity markets is the optimization of these resources, raising the question of how to dispatch the energy generated to meet the demand in a more economical and efficient way. With the objective of studying this scenario, this dissertation proposes a model for the economic dispatch of electric energy in minigrids. The model was developed considering five cases that correspond to different arrangements of minigrids. The simulations were implemented in the GAMS software, being performed for two scenarios. The first scenario considered a reduction of energy consumption from the grid of the Power Distribution Company; and the second considered an injection of electric energy into the grid of the Power Distribution Company. The results obtained show that the strategy applied to the proposed models was successful.